A systematic review of cognitive behavioral therapy-based interventions for comorbid chronic pain and clinically relevant psychological distress - Sanabria-Mazo, Juan P.; Colomer-Carbonell, Ariadna; Fernández-Vázquez, Óscar; Noboa-Rocamora, Georgina; Cardona-Ros, Gemma; McCracken, Lance M.; Montes-Pérez, Antonio; Castaño-Asins, Juan R.; Edo, Sílvia; Borràs, Xavier; Sanz, Antoni; Feliu-Soler, Albert; et al. (Frontiers in Psychology, 2023)
Objective: Chronic pain frequently co-occurs with clinically relevant psychological distress. A systematic review was conducted to identify the efficacy of cognitive behavioral therapy-based interventions for patients with these comorbid conditions.The systematic search was carried out in Medline, PsycINFO, Web of Science, and Scopus up to March 18 th , 2023. Four reviewers independently conducted screenings, extraction, and quality assessment.Results: Twelve randomized controlled trials and one non-randomized controlled trial involving 1661 participants that examined the efficacy of Cognitive Behavioral Therapy (nine studies), Mindfulnessbased Interventions (three studies), Acceptance and Commitment Therapy (one study), and Behavioral Activation Therapy for Depression (one study) were included. Compared to treatment as usual, six out of eight studies of traditional Cognitive Behavioral Therapy reported significant differences in the reduction of depressive symptoms at post-treatment (d from 1.31 to 0.18) and four out of six at followup (d from 0.75 to 0.26); similarly, five out of six reported significant differences in the reduction of anxiety symptoms at post-treatment (d from 1.08 to 0.19) and three out of four at follow-up (d from 1.07 to 0.27). Overall, no significant differences between traditional Cognitive Behavioral Therapy and treatment as usual were reported at post-treatment and follow-up in the studies exploring pain intensity and pain catastrophizing.The available evidence suggests that traditional Cognitive Behavioral Therapy may produce significant benefits for the improvement of depression, anxiety, and quality of life, but not for pain intensity and pain catastrophizing. More evidence is needed to determine the effects of MBI, ACT, and BATD.